Diversity of invertebrate trawl bycatch off Cuddalore, Parangipettai and Pazhayar, south-east coast of India - Murugesan, Perumal; Silambarasan, Arumugam; Purusothaman, Sambandamoorthy; Muthuvelu, Samikkannu; Anandaraj, Thirumeni (Indian Journal of Fisheries, 2013)
Invertebrate diversity along the south-east coast of India is rich and varied. Though many studies with respect to finfish bycatch resources have been carried out during yesteryears, only scanty information is available on invertebrate bycatch from tropical waters. The importance of invertebrates caught in the trawl bycatch has been recognised only recently by the scientific community, as the utility of invertebrate bycatch is manifold. The present study was undertaken to investigate and generate information on the diversity and species richness of invertebrates landed as trawl bycatch in Cuddalore, Parangipettai and Pazhayar along the south-east coast of India. The study was undertaken in the inshore waters (5- 35 m depth) of Cuddalore, Parangipettai and Pazhayar during Feb 2010 – Jan 2011. Altogether 66 species of invertebrates in Cuddalore, 75 in Parangipettai and 76 in Pazhayar were recorded during the study. The percentage composition revealed that in Cuddalore and Parangipettai, brachyuran crabs were the dominant group (37% and 46% respectively) followed by cephalopods (35% and 31% respectively), while in Pazhayar, gastropods dominanted (29%) followed by shrimps (24%) and other invertebrates were meagre. Diversity indices estimated showed variation between the regions. Shannon-Weiner diversity index ranged from 2.035 to 4.776; Margalef’s richness index from 2.306 to 6.782; Pielou’s evenness index varied from 0.488 to 0.957; taxonomic diversity varied from 45.08 to 83.53 and total phylogenetic diversity ranged from 733.33 to 1716.8.